A Safer Way to Harvest a Superthin Perforator Flap. Issue 3 (23rd February 2021) - Innocenti, Marco; Calabrese, Sara; Tanini, Sara; Malzone, Gerardo; Innocenti, Alessandro
Abstract : Summary: The updated knowledge of perforasome anatomy and the evolution of microsurgical techniques have enabled surgeons to safely harvest a thin flap. Recently, the anterolateral thigh perforator flap, the current workhorse in soft-tissue reconstruction, has started to be designed and harvested on the superficial fascia, which divides the deep from the superficial fat. This allows elevation of a very thin flap tailored to the defect. Faithful to the ultrathin concept, in an attempt to make flap dissection simpler and safer, the authors describe a revisited harvesting technique of superthin anterolateral thigh perforator flap. This study presents the outlined technique performed in 16 patients with complex soft-tissue defects after trauma or tumor ablation. All of them underwent primary reconstruction using superthin anterolateral thigh perforator free flaps by superficial fascia elevation harvested according to the described surgical procedure. Complications and functional outcomes were assessed. The authors' series of anterolateral thigh perforator superthin flaps demonstrated an overall 100 percent survival rate. Of 16 anterolateral thigh perforators, 12 (75 percent) had no complications and four (25 percent) had minor complications. No major complications such as total flap loss requiring additional salvage surgery were reported. In no case was secondary debulking performed. The superthin anterolateral thigh perforator flap harvested with the described approach was used successfully in microsurgical reconstruction, providing an excellent outer skin cover tailored to the defect. The dissection procedure was safe, quick, simple, and free of major complications. With minimal donor- and recipient-site morbidity, it provided great aesthetic results, avoiding secondary operations. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.